Análises morfológicas de lesões de pele de camundongos submetidos ao tratamento com extratos vegetais e plaquetas de descarte - Luciana Xavier Pereira (2013)
Morphological aspects of the healing process of skin wounds in mice were investigated in groups undergoing different topical treatments. The analyzes took into account parameters such as the characterization of cells (fibroblasts, myofibroblasts and mast cells) and extracellular matrix components (collagen and reticular fibers). The results were obtained from skin fragments collected from the lesion at nine and 21 days post treatment, from morphometric analyzes under light microscopy (LM) and the ultrastructure description by transmission electron microscopy (TEM). The animals were divided into 6 groups (G), treated as followed: gel base (G1); gel containing plant A (G2); gel containing plant A + platelets (G3); gel containing plant B (G4); gel containing Plan B + platelets (G5); gel containing platelets (G6). Treatment with platelets induced mast cell recruitment substantially different from what occurred in the animals treated with the complex platelets + plants in which there was no statistically significant difference about the number of mast cells compared to G1. It might indicate that the plants reverted to inflammatory reaction caused by mast by platelets. The results of reticular fibers showed that at nine days showed less deposition in the groups treated with the plant A (G2) and plant B (G4) and at 21 days there was no difference. Regarding to the collagen fibers the deposition was higher and uniform among treated groups at nine days, highlighting a greater deposition in the group treated with plant A (G2) at 21 days. Although detected in all groups, myofibroblasts occurred less frequently in the treated groups, which would be indicative of anti fibrotic action. The TEM analyzes allowed the detection of ultrastructural features of collagen fibrils and fibroblasts. Taking together, the results showed that there is an effective extracellular matrix renewal and antifibrotic control during the tissue repair process after application of treatments, mostly to treatments with plant A and plant B, which demonstrated better efficacy. This dual property leads to suggest them to treat lesions in addition to the benefit of raw materials are relatively easy access and low cost.